Network Selection Equilibrium in Heterogeneous Wireless Environment - Bakmaz, B. M. (Elektronika ir Elektrotechnika, 2013)
Service delivery in a heterogeneous wireless environment requires the selection of an optimal access network. In order that users could be always connected through the optimal available network, it is necessary to develop an adequate technique for its selection. This article presents the proposal of suitable network selection technique for heterogeneous wireless environment that is based on TOPSIS method when solving the multiple criteria decision making problems. The radio access networks in this model represent the alternatives, while the network parameters (network conditions, QoS level, security level, cost of service) are considered as the triggering criteria for determining the suitable network. Through simulation studies, we show the potential of entropy based TOPSIS model in optimal network selection process. DOI: http://dx.doi.org/10.5755/j01.eee.19.4.4058